2011
DOI: 10.1016/j.tins.2011.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Placing prediction into the fear circuit

Abstract: Pavlovian fear conditioning depends on synaptic plasticity at amygdala neurons. Here we review recent electrophysiological, molecular, and behavioral evidence suggesting the existence of a distributed neural circuitry regulating amygdala synaptic plasticity during fear learning. This circuitry, which involves projections from the midbrain periaqueductal gray (PAG) region, can be linked to prediction error and expectation modulation of fear learning as described by associative and computational learning models.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
231
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 260 publications
(243 citation statements)
references
References 105 publications
(140 reference statements)
12
231
0
Order By: Relevance
“…The first-level design matrix of each participant included separate regressors for each of the six conditions (CSA, CSB, CSAX, CSBY, CSX, CSY), which were modeled as delta functions at CS onset and were convolved with the canonical hemodynamic response function. We decided to focus our analysis on the well studied enhancement of CSrelated amygdala responses in aversive learning (Quirk et al, 1995;LaBar et al, 1998;Paton et al, 2006) and did not investigate US-related responses, as evidence for the amygdala coding prediction errors in aversive learning is scarce (Belova et al, 2007;Delgado et al, 2008b;Li et al, 2011;McNally et al, 2011). Nevertheless, we wanted to account for the variance induced by US-related responses and therefore created similar regressors at US onset.…”
Section: Methodsmentioning
confidence: 99%
“…The first-level design matrix of each participant included separate regressors for each of the six conditions (CSA, CSB, CSAX, CSBY, CSX, CSY), which were modeled as delta functions at CS onset and were convolved with the canonical hemodynamic response function. We decided to focus our analysis on the well studied enhancement of CSrelated amygdala responses in aversive learning (Quirk et al, 1995;LaBar et al, 1998;Paton et al, 2006) and did not investigate US-related responses, as evidence for the amygdala coding prediction errors in aversive learning is scarce (Belova et al, 2007;Delgado et al, 2008b;Li et al, 2011;McNally et al, 2011). Nevertheless, we wanted to account for the variance induced by US-related responses and therefore created similar regressors at US onset.…”
Section: Methodsmentioning
confidence: 99%
“…Henson & Gagnepain, 2010;McNally et al, 2011). According to such models, a constant filtering of sensations by top-down predictions and a parallel updating of the latter based on prediction errors (signals representing the mismatch between predictions and sensations), with the ultimate goal of minimizing prediction errors, is an imperfect but highly efficient means of perceiving sensations (Rao and Ballard, 1999).…”
Section: Embodied Mentalization: a Free Energy Perspectivementioning
confidence: 99%
“…There was no freezing during the first CS -footshock US. Rats were sacrificed after the first Stage II CS -footshock US pairing and pMAPK immunoreactivity (pMAPK-IR) was studied in several brain regions linked to fear learning, including the prefrontal cortex, amygdala, midline thalamus, nucleus accumbens, hypothalamus, and periaqueductal gray (PAG) (McNally et al 2011); the results are shown in Figure 2. Stage II behavioral data were not recorded due to technical difficulties with recording equipment.…”
Section: Experiments 1bmentioning
confidence: 99%